Histological Analysis of Bone Callus in Delayed Union Model Fracture Healing Stimulated with Pulsed Electromagnetic Fields (PEMF) - U. Umiatin; Ismail Hadisoebroto Dilogo; Puji Sari; Sastra Kusuma Wijaya (Scientifica)
Delayed union and nonunion fractures are clinical challenges for orthopedic surgeons. The development of fracture complications, such as delayed union and nonunion fractures, is still difficult to predict. Various methods are being investigated to improve fracture healing and prevent complications in patients. There are various methods to promote fracture healing, broadly divided into biological, chemical, and physical methods. One of the most widely used physical methods to promote fracture healing is the pulsed electromagnetic field (PEMF). This study aimed to evaluate the healing process of delayed union fracture after being stimulated by PEMF. Twenty-four rats were randomly divided into two groups: the control group (n = 12) and the PEMF group (n = 12). Delayed union fracture was performed on the left femur of all rats. Subsequently, the PEMF group was given PEMF stimulus with a magnetic field intensity of 1.6 mT and a frequency of 50 Hz for 4 hours/day and 7 days/week. The fracture healing process was evaluated on days 5, 10, 18, and 28 based on the bone callus histology using safranin O fast green (SOFG) staining. The results of the histological analysis showed that bone cartilage was higher in the PEMF group than in the control group throughout the observation period. In addition, the PEMF group had less fibrous tissue at the beginning of the healing. This finding indicates PEMF stimulation has an effect on inducing osteogenesis on fracture healing and reducing the risk of delayed union.